Efficacy of High Dose Tranexamic Acid in Decreasing Bleeding after Cardiac Surgery for Cyanotic Congenital Heart Disease in Children Less than Ten Kilo Body Weight - Sampathkumar, Saranya V.; Raju, Vijayakumar; Balakrishnan, Soundaravalli; Moorthy, Saigopalakrishnan M.; Arul, Anandhi; Muthuswamy, Kalyana S.; Srinivasan, Muralidharan (Scientific Research, 2018)
Background: To determine the effect of high dose tranexamic acid in decreasing immediate postoperative bleeding in children less than ten kilo body weight after complex cardiac surgery and also to evaluate the safety of high dose in small children. Methods: Between January-December 2015, 25 children weighing less than ten kilogram body weight underwent complex cardiac surgery for cyanotic congenital heart disease. All children were given dose of 100 mg/kg tranexamic acid at the time of anaesthetic induction and also 100 mg/kg into the CPB prime. The Median age and weight was 80 days (3 - 365) and 4.69 kg (2.4 - 7.8) respectively. The Median preoperative Hb was 10 g/dl (9.6 - 19.5 g/dl). Cardiac surgery included total intracardiac repair for TOF in 10 pts (40%), TAPVC repair in 6 (24%), arterial switch operation in 6 pts (24%), BD glenn in 1, repair of DORV with VSD in 1 and VSD closure with scimitar vein reimplantation in 1 pt. Median CPB time was 127 minutes (97 - 343) and cross clamp time was 99 (67 - 200) minutes. Moderate to deep hypothermia was maintained in all with median temperature of 24˚C (18 - 32). Three children (12%) had elective open chest in view of anticipated bleeding. Results: The Median postoperative drainage was 127 ml, (range 10 - 1250 ml). The median postoperative use of whole blood was 95 ml (range 10 - 275), packed cell was 187 ml (range 50 - 400 ml), frozen plasma was 88 ml (range 30 - 170), platelet concentrate was 57 ml, (range 10 - 100 ml) and cryoprecipitate was median 47.5 ml, (range 30 - 80 ml). No neurological dysfunction and renal dysfunction has been observed in any of the pts. Out of 4 mortalities (16%),only one was attributed to bleeding (4%) due to usage of ECMO. No late neurological or renal dysfunction has been observed in remaining 21 pts on follow up. Conclusion: High dose Tranexamic acid can be safely used in small children during complex cardiac surgery with significant reduction in postoperative bleeding and blood product usage without any higher incidence of neurological, renal dysfunction or myocardial infarction
Keywords: Pediatric Cardiac Surgery; Bleeding; Antifibrinolytics; Tranexamic Acid; Renal Dysfunction; Neurological Dysfunction